Elite athletes` and support staffs` experiences and perceptions of long-haul travel, and the self-management strategies they use - Rossiter, A., Comyns, T. M., Sherwin, I., Nevill, A. M., Warrington, G. D: (International Journal of Sports Science & Coaching, 2023)
Elite athletes and their support staff are often required to travel for international competitions all over the globe, however little is known about their experiences of long-haul (LH) travel and its perceived effects on performance. The aim of this study was to explore elite athletes` and support staffs` perception of symptoms experienced following LH travel and the self-management strategies they used to mitigate these symptoms. Elite athletes and support staff (n = 88), who had embarked on an LH flight (> 8 hours) in the previous 2 years for training or competition, completed a survey examining their perceptions of LH travel, symptoms experienced following the flight(s) and strategies they implemented to minimise the symptoms. Associations between symptoms experienced and travel strategies used with participant and journey characteristics were examined by Chi-squared tests. LH travel was widely perceived by participants to be disruptive to physical (86.4%) and mental performance (72.7%) and to increase the risk of illness and injury (86.4%). The most common symptoms experienced were related to fatigue and disruption to sleep. All participants implemented strategies to help mitigate the negative consequences of LH travel. Moving and stretching regularly in-flight and simple strategies for aligning the body clock to destination time were most prevalent. The study findings will allow the translation of research to better inform future guidelines that address the unique needs and priorities of elite athletes and support staff as they embark on LH travel for training and competition with a view to optimising performance outcomes.